Bravo Sánchez,Alex Darling(2023)DISTRIBUCIÓN Y ABUNDANCIA DEL CARACOL GIGANTE AFRICANO (Lissachatina fulica) EN DISTINTOS CULTIVOS DE LA FINCA EXPERIMENTAL LA MARÍA.Quevedo.UTEQ.58p. - Bravo Sánchez , Alex Darling (2023)
The giant African snail (Lissachatina fulica), one of the most harmful invasive species globally, has generated alarm in Ecuador due to its role as an intermediary in the transmission of parasites and its negative impact on commercial plantations. This research aims to explore the distribution and abundance of this species in several crops of the experimental farm "La María", located in the province of Los Ríos, Ecuador, in order to identify which of the common Ecuadorian coastal crops is preferred by this mollusk. A detailed analysis of the different crops was carried out, showing the presence of the snail in the African palm plantation, in the radish crop, and in the garden areas with fruit and ornamental plantations. This research was carried out during the last days of January 2023, coinciding with the winter season, a period in which snail activity intensifies. A manual method based on a system of transects and quadrants was used to count the snails. The results indicated that the African palm harbored the greatest number of individuals of this species per square meter. An average shell length of 52.80 mm of the giant African snail was recorded in the areas studied, suggesting that these individuals are in the sub-adult stage and that the level of establishment of the mollusk in the crops analyzed is medium-high. The conclusive results indicate that the African palm crop is preferred by the giant African snail, since it has a density of 2.27 individuals/m2 and possesses environmental conditions conducive to the establishment of this species. Based on the findings, it is concluded that the experimental farm "La María" is a scenario in which the presence of the giant African snail is considerable, especially in the African palm crop